Total Fitness in 30 Minutes a Week - Morehouse, Laurence E., 1913-1995 (New York Pocket Books, 1976)
Presents an adaptation of the book of the same title by Laurence E. Morehouse, narrated by Leonard Gross and the author. Explains a five-point program that leads to excellent physical conditioning through pulse-rated exercises
Keywords: Physical fitness -- Exercise -- Pulse